2015
DOI: 10.1002/clc.22437
|View full text |Cite
|
Sign up to set email alerts
|

Conicity Index and Waist‐to‐Hip Ratio Are Superior Obesity Indices in Predicting 10‐Year Cardiovascular Risk Among Men and Women

Abstract: Background: Central obesity has been recognized as a main risk factor for cardiovascular (CV) events. Three popular central obesity indices are waist circumference, waist-to-hip ratio (WHR), and waist-to-height ratio; abdominal volume index and conicity index are 2 recent novel obesity indices. The main aim of this study is to determine the performance of these indices to best predict 10-year CV events. Hypothesis: Some obesity indices can be used to predict cardiovascular risk. Methods: In total, 3199 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 29 publications
2
60
0
4
Order By: Relevance
“…The OR at the 95% confidence interval was 4.66 and 4.39, while, the kappa coefficient was 0.18 and 0.10. There were slightly different cutoff values for young Caucasian Sicilian population of 2.52 (age <30 years) and 2.23 (age ≥30 and <42 years) were reported by Amato et al34 Motamed et al35 stated the same finding for the discriminatory accuracy of CI for 10-years FS and ASCVD scores among men. However, the accuracy of CI among women was not consistent with our results.…”
Section: Discussionmentioning
confidence: 79%
“…The OR at the 95% confidence interval was 4.66 and 4.39, while, the kappa coefficient was 0.18 and 0.10. There were slightly different cutoff values for young Caucasian Sicilian population of 2.52 (age <30 years) and 2.23 (age ≥30 and <42 years) were reported by Amato et al34 Motamed et al35 stated the same finding for the discriminatory accuracy of CI for 10-years FS and ASCVD scores among men. However, the accuracy of CI among women was not consistent with our results.…”
Section: Discussionmentioning
confidence: 79%
“…20 The use of BMI in older adults can result in overweight and obesity classification errors as a result of inaccuracies and difficulties of measuring the height and lean body mass reduction that occurs during aging. Regarding the conicity index, for example, studies including adults and older adults have shown that its accuracy to discriminate high coronary risk is higher than other central distribution indicators of fat, such as WHtR, especially in women, 25,26 and similar to WHR. 19 Hip circumference could be used as an indicator of total body adiposity, especially in situations where it is not possible to measure the weight and height, but its use is limited because there are no parameters for its classification.…”
Section: Discussionmentioning
confidence: 99%
“…24 Considering the knowledge gaps about ABSI, other measures can be used to assess the body fat distribution in older adults. Regarding the conicity index, for example, studies including adults and older adults have shown that its accuracy to discriminate high coronary risk is higher than other central distribution indicators of fat, such as WHtR, especially in women, 25,26 and similar to WHR. 27 Although the WHR was not variable strongly correlated with factor 2, it could be used as an indicator of body fat distribution in situations in which obtaining the height is not possible with the advantage of it being obtained quickly and easily compared with the other indices.…”
Section: Discussionmentioning
confidence: 99%
“…WC was measured to the nearest centimeter at the level of the umbilicus after expiration as the participant stood and breathed normally, and HC was measured as the widest circumference around the buttocks. The abdominal volume index (AVI), which measures adipose tissue in viscera and abdominal organs, was calculated as follows: AVI={}2×WC20.25em()cm+0.7×WCcmHCcm2/1000. …”
Section: Methodsmentioning
confidence: 99%